Geometry considerations for use of Bi-2223 - Stavrev, S. (IEEE Transactions on applied superconductivity)
In typical power applications, Bi-2223 conductors carrying AC current will be subjected to external magnetic fields whose orientation and conductor's geometry are of major significance for the AC loss magnitude. This paper investigates the influence of the geometry and aspect ratio of nontwisted Bi-2223 conductors in reducing the AC loss for such applications. A numerical model of high-Tc materials has been used in finite-element-method (FEM) simulations. The model incorporates power-law E-J characteristics with Jc and n defined by both parallel and perpendicular local magnetic field components. It allows computations of field and current distributions with transport current and/or applied field of any orientation. Monofilamentary tapes of rectangular and elliptical geometry with anisotropic Jc(B), as well as square and round wires with isotropic Jc(B) have been used for simulations under various operating conditions. A comparison between AC losses, magnetic field, and current distributions in the tapes and wires is presented